Tantangan Penegakan Hukum di Era Globalisasi Digital: Strategi Nasional Menghadapi Kejahatan Siber Lintas Batas - Islami, Zahra Pitaloka (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid advancement of digital technology and cyber globalization has accelerated the emergence of a new order of social, economic, and political interactions that increasingly depend on cross-border data flows, thereby giving rise to new configurations of crime that are no longer subject to the physical territorial boundaries of the state. In this context, cybercrime, data theft, attacks on critical infrastructure, misuse of digital identities, as well as various forms of manipulation of information systems challenge the classical paradigm of national law enforcement, which rests on the principles of territoriality, personality, and the protection of state interests that were designed for an analog world. The situation becomes even more complex when offenders, victims, servers, service providers, and the impacts of crime are dispersed across multiple jurisdictions, while national legal instruments, criminal procedure rules, and the institutional capacity of law-enforcement agencies still operate within a framework that assumes that the locus and tempus delicti can be clearly determined within a single sovereign territory. This paper seeks to identify the weaknesses of the national legal system in responding to global cybercrime and to formulate law-enforcement strategies that are adaptive to the characteristics of the digital space, which does not recognize state borders, by analyzing the dimensions of legal substance, institutional structure, and legal culture that shape the way the state responds to these threats. The approach employed is normative juridical, supported by a criminal-policy perspective, by revisiting the principles of jurisdiction, extradition, mutual legal assistance, and due process of law in the context of digital transformation, while at the same time weighing the need for regulatory harmonization, the strengthening of the technical capacity of law-enforcement agencies, and the establishment of agile cross-border cooperation mechanisms that nonetheless respect human rights and the protection of personal data. The results of the discussion show that an effective national law-enforcement strategy in the era of digital globalization cannot stop at merely revising individual criminal provisions, but instead presupposes a comprehensive reconstruction of how the state understands sovereignty in cyberspace, designs procedures for electronic evidence, manages cooperation with global private actors, and integrates the role of society in preventing and reporting cybercrime. This paper then offers a series of normative and practical recommendations that include updating the regulatory framework, strengthening institutions, developing multi-stakeholder digital governance, and improving digital literacy as efforts to build a law-enforcement architecture that is more responsive, adaptive, and just amid the challenges of digital globalization.